Pengaruh Komitmen dan Kepercayaan terhadap Kepuasan Nasabah Bank Syariah di Surabaya - Erwan Aristyanto; Aditya Surya Nanda; Andi Farouq Hasan (Perisai : Islamic Banking and Finance Journal, 2019)
Intense competition between banks is increasingly tight good conventional banks as well as Islamic banks. The rivalry has led banks to get competitive strategies do customers. Strategy all aimed at satisfying the customer's bank. The key competitive advantage in a situation full of competition is the ability of the bank in improving customer satisfaction. Customer satisfaction will be the key to success, not only in the short term but sustain- able competitive advantage. The purpose of this research is to find out and analyse the influence the commitment and trust of customer satisfaction on Sharia in Surabaya. The population in this study is bank syariah in Surabaya and the number of samples as much as 95 clients. The technique of sampling by using purposive sampling namely sampling with certain considerations. Design research is quantitative with the hypothesis. Data analysis techniques using multiple linear regression using SPSS 23.